Constructing the Problem in Marx’s Political Philosophy - Fengyu, Zang (Bollettino Filosofico, 2025)
This article explores Marx’s political philosophy, advocating for a normative and scholarly approach that transcends traditional interpretations. It shows how Marx’s analysis of contemporary political issues leaves behind classical metaphysical frameworks and thereby gains practical relevance. The study highlights the necessity and possibility of systematically reconstructing Marx’s political philosophy, demonstrating its grounding in historical materialism and critique of capital logic. The domains of Marx’s political philosophy are examined, focusing on human emancipation, community, and justice. The article concludes by asserting today’s relevance of Marx’s ideas, underscoring their enduring impact on understanding and transforming the world. Keywords: Critique of Political Economy, Human Emancipation, Marx’s political philosophy, Problem Consciousness, True community